Redescribing, But Really, Finally Moving on From Israelite Origins - Tobolowsky, Andrew (Method & theory in the study of religion, 2023)
Burton Mack’s 1996 article “On Redescribing Christian Origins” was a classic of the discipline. In my view, one of its most enduring contributions is its recognition that the centrality of the New Testament’s view of Christian Origins survives despite a growing recognition that, technically, it ought to be sidelined – that it is protected by a “ring of fire.” Further, he argued that the perseverance of this centrality was a major factor inhibiting the influence of New Testament studies on other disciplines. In this essay, I argue that the centrality of the Hebrew Bible’s vision of Israelite origins as a starting point for contemporary debates, even among those who regard it as a fiction, is characterized by a similar avoidance of certain necessary recognitions and is inhibiting to a similar degree.